2007
DOI: 10.1002/jcc.20794
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensionality of delocalization indices and nucleus independent chemical shifts in polycyclic aromatic hydrocarbons

Abstract: The aromaticity and local-aromaticity of a large set of polycyclic aromatic hydrocarbons (PAHs) is studied using multicenter delocalization indices from generalized population analysis and the popular nucleus independent chemical shift (NICS) index. A method for the fast computation of the NICS values is introduced, using the so-called pseudo-pi-method. A detailed examination is made of the multidimensional nature of aromaticity. The lack of a good correlation between the NICS and the multicenter delocalizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
84
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 87 publications
(92 citation statements)
references
References 61 publications
2
84
1
Order By: Relevance
“…Through statistical analysis, the present authors have previously shown that for a large set of PAH, the NICS values can be derived from MCBI, refuting the need to invoke a local analogue of the multidimensionality of aromaticity. It was also shown that ring current maps derived from MCBI, agree very well with ab initio computed ring current maps [1,22,23] .…”
Section: Introductionsupporting
confidence: 55%
See 4 more Smart Citations
“…Through statistical analysis, the present authors have previously shown that for a large set of PAH, the NICS values can be derived from MCBI, refuting the need to invoke a local analogue of the multidimensionality of aromaticity. It was also shown that ring current maps derived from MCBI, agree very well with ab initio computed ring current maps [1,22,23] .…”
Section: Introductionsupporting
confidence: 55%
“…The MCBI for all these molecules were calculated using the Pseudo-π approach [1,[28][29][30] . The MCBI were computed using the in home developed Kekule program which uses the Gaussian-03 [31] formatted checkpoint file.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations